Summary of Recommendations of State Hospital Boards of Trustees Submitted to Director of Mental Hygiene (1960)
This four page document is the summary of recommendations of state hospital boards of trustees submitted to director of mental hygiene. In this report each trustee who oversees a state hospital has written various recommendations in which their hospital can be improved. For example the Camarillo State Hospital, recommended that there exist an increase in salary structure for medical staff and employees in nursing services.They also recommended a great public education in order to encourage acceptance of the hospitalized patient as an "individual", a member of a family unit in a community.